Article RETRACTED due to manipulation by the authors - Kukuh Wahyudin Pratama; Suharjana Suharjana; Ahmad Nasrulloh; La Ode Maklum Sabrin; Doni Pranata; Septadi Hanif Pambayu; Deni Hardianto; Panggung Sutapa; Rizqie Auliana; Manil Karakauki; Danarstuti Utami; Ardi Riyana; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
RED-S is a contraindication for women in the sport. The purpose of the exercise was originally getting results in the form of a healthy and a fit body, but the female athletes when exercise is done with intensity is too high then suffered great mental distress that would arise RED-S disease include anorexia nervosa, amenorrhea, and osteoporosis. This study aims to identify the RED-S in women swimmer athletes. The results showed that the identification of RED-S in the women swimmer athlete is as follows: In objective based on the control of anorexia nervosa in detail that there were 26 (100%) athletes who entered in categories of anorexia nervosa. While the detailed control of amenorrhoea that there are 25 (96.15%) athletes who fall into the category of secondary amenorrhoea and 1 (3.85%) athletes who fall into the category of primary amenorrhoea. Then in the control of Osteoporosis in detail there are 0 (0%) athletes who fall into the category of high osteoporosis, 12 (46.15%) athletes who fall into the category of moderate osteoporosis, and 14 (53.85%) athletes who fall into the category of low osteoporosis. In Subjective based on the tendency of the RED-S, as many as three athletes (11.54 %) were in the category of very high, 3 athletes (11.54 %) were in the high category, 13 athletes (50.00%) were in the category of being, 5 athletes (19.23 %) were categorized as low, and 1 athlete (3.85%) were categorized as very low. While based on the RED-S risk factors, as many as four athletes (15.38%) were in the category of very high, 5 athletes (19.23%) were in the high category, 12 athletes (46.15%) were in the category medium, 2 athletes (7.69 %) were included in the low category, and 3 athletes (11.54%) were in the category of very low.